Respuesta :
Answer:
Kendal will be 60 meters away from the library after 80 seconds and again after 100 seconds.
Step-by-step explanation:
|540 − 6t| = 60.
Solve an absolute value equation by writing it as two separate linear equations and solving each one:
540 − 6t = -60 540 − 6t = 60
-6t = -600 -6t = -480
t = 100 t = 80
Answer
Kendal will be 60 meters away from the library after 80 seconds and again after 100 seconds.
Step-by-step explanation:
Let t represent time in seconds. Kendal is riding at a rate of 6 meters/second, so 6t represents the distance she can travel in t seconds.
The distance to the library is 540 meters. Because Kendal is riding toward the library, subtract 6t from 540 to find the distance between Kendal and the library before she passes it:
540 − 6t.
Kendal will be 60 meters away from the library twice, once as she approaches it and again after she passes it. The absolute value of the difference 540 − 6t represents Kendal's distance from the library. To find the time after which Kendal will be 60 meters away from the library, form an absolute value equation:
|540 − 6t| = 60.
Solve an absolute value equation by writing it as two separate linear equations and solving each one:
540 − 6t = -60 540 − 6t = 60
-6t = -600 -6t = -480
t = 100 t = 80
Let t represent time in seconds. Kendal is riding at a rate of 6 meters/second, so 6t represents the distance she can travel in t seconds.
The distance to the library is 540 meters. Because Kendal is riding toward the library, subtract 6t from 540 to find the distance between Kendal and the library before she passes it:
540 − 6t.
Kendal will be 60 meters away from the library twice, once as she approaches it and again after she passes it. The absolute value of the difference 540 − 6t represents Kendal's distance from the library. To find the time after which Kendal will be 60 meters away from the library, form an absolute value equation:
|540 − 6t| = 60.
Solve an absolute value equation by writing it as two separate linear equations and solving each one:
540 − 6t = -60 540 − 6t = 60
-6t = -600 -6t = -480
t = 100 t = 80